2013
DOI: 10.1002/cbic.201300163
|View full text |Cite
|
Sign up to set email alerts
|

The TEAD4–YAP/TAZ Protein–Protein Interaction: Expected Similarities and Unexpected Differences

Abstract: The Hippo pathway controls cell homeostasis, and its deregulation can lead to human diseases. In this pathway, the YAP and TAZ transcriptional cofactors play a key role in stimulating gene transcription through their interaction with the TEAD transcriptional factors. Our study of YAP and TAZ peptides in biochemical and biophysical assays shows that both proteins have essentially the same affinity for TEAD. Molecular modeling and structural biology data suggest that they also bind to the same site on TEAD. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 34 publications
8
122
0
Order By: Relevance
“…Although YAP and TAZ have essentially the same affinity for TEAD (TEA domain family member 1), differences have been found in the ways in which they interact with TEAD (56). Recent evidence suggests that YAP and TAZ do not compensate for each other (57), as evidenced by the findings that YAP and TAZ knockout mice show different phenotypes and that the phenotypes of YAP and TAZ knockdowns cannot be compensated for by the other gene (58).…”
Section: Discussionmentioning
confidence: 99%
“…Although YAP and TAZ have essentially the same affinity for TEAD (TEA domain family member 1), differences have been found in the ways in which they interact with TEAD (56). Recent evidence suggests that YAP and TAZ do not compensate for each other (57), as evidenced by the findings that YAP and TAZ knockout mice show different phenotypes and that the phenotypes of YAP and TAZ knockdowns cannot be compensated for by the other gene (58).…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the TEAD-binding domain is conserved between TAZ and YAP, TAZ lacks the PxxΦP motif. Thus, differences between TAZ and YAP binding to TEAD transcription factors exist, which is supported by recent molecular modeling studies and mutational analysis (Hau et al, 2013). However, whether these differences translate to disparate TAZ/YAP activities in vivo is yet to be determined.…”
Section: Box 1 Evolutionary Conservation Of the Hippo Pathwaymentioning
confidence: 93%
“…YAP1, a transcription factor, is an ovarian cancer oncogene in the previous studies, but the core of the mammalian Hippo pathway is composed of two kinases complexes: the MST1-2/Sav1 complex and the LATS2/MOB complex [21,39,40]. The previous study showed that YAP1 has no transcriptional activity and its actions are dependent on downstream transcriptional factors [41,42]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%